From fear to recovery: Investor sentiment, macroeconomic shocks, and tourism stock volatility in China - Aziz Ullah; He Biao; Mahfuzur Rahman; Assad Ullah (Annals of Tourism Research Empirical Insights, 2025)
This research investigates the impact of investor sentiment and macroeconomic shocks on the volatility of China's tourism stocks during the COVID-19 recovery period, specifically from March 2020 to December 2022. By analyzing daily data from 20 publicly listed tourism companies using GARCH family models, the study distinguishes between a Crisis Phase (from March 2020 to February 2022) and a Recovery Phase (from March to December 2022). The findings indicate that during the Crisis Phase, investor sentiment and anxiety related to the pandemic heightened volatility, resulting in a 6.2~% contraction in tourism GDP. After March 2022, the impact of pandemic-related fears began to diminish. The analysis also reveals bidirectional volatility spillovers among different tourism subsectors, indicating that market sentiment plays a significant role in contributing to this volatility. The study highlights the importance of investor education and institutional reforms in mitigating herd behavior and stabilizing a key sector of China's economy.
Keywords: 330; Chinese tourism industry; GARCH models; Investor sentiment; Post-pandemic; Tourism stocks; Volatility